2019
DOI: 10.1186/s40794-019-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and seven year trend of malaria in North West Tigrai: 2012–2018, Ethiopia; 2019

Abstract: Background Malaria is a serious public concern in Ethiopia, 75% of the land and 60% of the population are exposed to the disease. The disease has been consistently reported as one of the top three leading causes of outpatient visits, admissions, and deaths among all age group in Ethiopia. However, there is no published data to date regarding the trends of malaria in north western Tigrai, northern Ethiopia. Hence, knowing the trends of malaria prevalence in this area is essential to design appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
7
13
1
Order By: Relevance
“…Here, the prevalence was markedly lower than previous studies conducted in several parts of the country such as in Dembia (21.8%), 8 Dembecha (16.3%), 21 Guba (51.0%), 19 Sibu Sire (20.1%), 22 Arjo-Didessa sugar development site (33.4%), 23 Harari (46.9%), 24 Chalia district (7.6%), 25 Abeshge (33.8%), 26 and Bale Zone (66.7%). 27 The prevalence of the present study was also relatively lower than the findings from other parts of Ethiopia like Northwest Tigray (7.0%), 6 Wereta (5.4%), 28 Kombolcha (7.5%), 18 Ataye (8.4%), 29 Halaba (9.5%), 7 Wolkite (8.6%) 30 and Arsi Negelle (11.5%). 31…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Here, the prevalence was markedly lower than previous studies conducted in several parts of the country such as in Dembia (21.8%), 8 Dembecha (16.3%), 21 Guba (51.0%), 19 Sibu Sire (20.1%), 22 Arjo-Didessa sugar development site (33.4%), 23 Harari (46.9%), 24 Chalia district (7.6%), 25 Abeshge (33.8%), 26 and Bale Zone (66.7%). 27 The prevalence of the present study was also relatively lower than the findings from other parts of Ethiopia like Northwest Tigray (7.0%), 6 Wereta (5.4%), 28 Kombolcha (7.5%), 18 Ataye (8.4%), 29 Halaba (9.5%), 7 Wolkite (8.6%) 30 and Arsi Negelle (11.5%). 31…”
Section: Discussioncontrasting
confidence: 48%
“…Nevertheless, males were more affected than females, which is consistent with previous studies in Ethiopia. 6–8 , 19 , 21 , 23 , 27 This gender difference in malaria prevalence could be since males are frequently bitten by mosquitoes due to their behavioral differences such as working outdoors, little chance of sleeping under bed nets, and travel to endemic areas for labor work. 48 Moreover, hormonal differences might play the role in such a way that testosterone was associated with decreased adaptive immunity against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning malaria cases detected by species from the blood lm, the present study revealed that out of 47,016 con rmed malaria cases 53%, 41% and 6% showed P. falciparum, P.vivax and mixed infection, respectively. The present study nding is in agreement with the previous reports (Tesfaye et al, 2018;Berhe et al, 2019;Alkadi et al, 2020). The predominance of P. falciparum was consistent over the ve years with slight seasonal variation.…”
Section: Discussionsupporting
confidence: 94%
“…Malaria is a serious public concern in Ethiopia, 75% of the land and 60% of the population are exposed to the disease. The disease has been consistently reported as one of the top three leading causes of outpatient visits, admissions, and deaths among all age group in Ethiopia ( Berhe et al., 2019 ). There are about 5–6 million annual confirmed malaria cases in Ethiopia ( FMOH, 2012 ).…”
Section: Introductionmentioning
confidence: 99%